Les pesons antiques en terre cuite de Châteaubleau (Seine-et-Marne) et de sa région - Régis Bontrond (Revue Archéologique du Centre de la France)
The ancient settlement of Châteaubleau (Seine-et-Marne) has delivered a significant set of triangular terracotta spinel. Their study highlighted its homogeneity and thus, permit to establish a local typology. The presence of many brands is one of the originalities. It allows us to tackle different issues, the first of which is the location of their place of production. But it also offers the opportunity to question or re-examine the function of these objects, perhaps too systematically attributed to a weaving activity. Lastly, this set has been placed in its regional context, in order to evaluate the extension area of this type of spinel, for a long time considered absent or anecdotic during Antiquity.